The Female Genital Tract on MDCT: A Pictorial Review of Normal Anatomy and Incidental Abnormalities - Shrea Gulati; Vinita Rathi; Shuchi Bhatt; Sandhya Jain (Thieme Medical and Scientific Publishers Pvt. Ltd., 2022)
Abstract Purpose This article aims to review the pertinent anatomy and the incidental abnormalities involving the female genital tract on multidetector computed tomography (MDCT) through a pictorial review. Methods The review is based on critical analysis of the existing literature as well as our experience in dealing with incidental lesions involving the female genital tract. Results The lack of awareness regarding the normal appearances of the female pelvis on MDCT can puzzle the inexperienced radiologist and create management dilemmas for the treating clinician. It is important for radiologists to recognize normal appearances of the female genital tract on MDCT to prevent misinterpretation as pathology. The identification of incidentalomas of the female genital tract on CT can further guide whether additional workup is required or not. This pictorial review familiarizes radiologists with the normal appearances of the female genital tract on MDCT and a few common incidentalomas. Conclusion It is imperative for a clinical radiologist to be familiar with the anatomy and common incidental lesions involving the female genital tract.